DAYA TARIK OBJEK WISATA BENTENG PORTUGIS DI PULAU CINGKUAK NAGARI PAINAN SELATAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN. - Yulandari, Nami; Erita, Yeni; Juita, Erna (Pendidikan Geografi, 2013)
This study aims to describe the tourist attraction. In Nagari Cingkuak Island South Painan Kecematan IV Jurai South Coastal District. The research is qualitative, the data source is taken words and actions that come from the people who know the research problems. Subject of this research is the Department of Tourism, Wali Nagari South Painan District IV Jurai, communities, traders, visitors, youth, attractions Portuguese fort in Cingkuak Island. Research subjects taken by purposive sampling technique. Techniques of data collection through interviews, observation and photography. Techniques of data analysis is data reduction, data display and data interpretation. Technique to test the validity of the data used extension participation, persistence observation, triangulation. The results clarify that: Fascination Regarding (facilities, cleanliness, safety, beauty, welcoming, coolness, orderly, soufenir) Attractions: Portuguese fort in Nagari Cingkuak Island South Painan District IV Jurai South Coastal District. Viewed from the cleanliness, facilities, and soufenir not reflect Attractions Attractions: Portuguese fort in Nagari Cingkuak Island South Painan District IV Jurai South Coastal District. If viewed from the safety, coolness, beauty, orderly, and welcoming has reflected Fascination Attractions: Portuguese fort in Nagari Cingkuak Island South Painan well, because visitors feel comfortable there.